Predictive Accuracy of Biochemical and Anthropometric Indices for Metabolic Syndrome in Children with Obesity: A Comparative Study - Cihad Dundar (Life)
Children with obesity, regardless of gender, are a high-risk population that requires ongoing monitoring not only for present obesity and metabolic syndrome (MetS) but also future risks of metabolic, cardiac, musculoskeletal, and psychiatric complications. Data from a cohort of 185 obese children who underwent a second follow-up in 2019 were used for this retrospective study. The study cohort consisted of 94 boys and 91 girls who were elementary school students with a mean age of 10.2 ± 0.5 years. Following anthropometric and biochemical assessments, the cardio metabolic index (CMI), visceral adiposity index (VAI), triglyceride–glucose index (TyGI), and homeostasis model assessment of insulin resistance (HOMA-IR) were calculated. The overall prevalence of MetS was 19.5% (12.8% in boys and 26.4% in girls). According to the receiver operating characteristic curve analysis, CMI, VAI, and TyGI performed significantly better than HOMA-IR in identifying MetS. CMI was the most accurate predictor of MetS, as indicated by the highest area under the curve value, in both genders. In conclusion, our findings suggest that the CMI can serve as a practical, efficient, and affordable screening tool for the ongoing monitoring of childhood obesity in both daily endocrine clinical practice and primary care settings.